ANALISIS RASIO LIKUIDITAS KEUANGAN PADA PERUSAHAAN PERUM PERUMNAS WILAYAH VII MAKASSAR SEBAGAI ALAT PENGAMBILAN KEPUTUSAN - Tamsil Tamsil (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
The research objective was to determine the performance of the Company's financial perspective Perumnas Region VII Makassar, using financial ratio analysis of the company's year-to-year (2006-2010) by using the liquidity ratio. The method of analysis used in this study is the Ratio Analysis Liquidity Ratios Liquidity namely; Current ratio The current ratio is used to determine ability to meet short-term liabilities ratio and cash ratio measures the company's ability to pay its current debts with the cash equivalent of cash. The results showed that the liquidity ratio for 5 (five) years, from 2006 s / d 2010 figures current ratio shows the percentage of positive value suggests that it is the obligation / debt can be secured by the company's current assets, so that the company can be said to be illiquid.